Sociotechnical Imaginaries of Digitally Altered Minds in 2050: Functions, Citizens, and Societal Tensions - Ojell-Järventausta, Terho; Belousov, Anatolii; Bujić, Mila; Macey, Joseph; Hamari, Juho (United States, 2026)
Adding to the list of practices permeated by digital technologies, in recent years, domains related to altered states of consciousness (ASC) (e.g. psychedelic experiences) have also seen an increasing number of digital implementations. While implementations at the intersection of HCI and ASC mostly represent weak signals, there is a need for anticipatory research to explore the possible implications of digitally induced altered states of consciousness (DIAL). To address this, we adopted the Futures Clinique method to map out DIAL-related sociotechnical imaginaries through two futures workshops, capturing collective anticipations expressed in narrative scenarios created by participants. These scenarios were then analysed using reflexive thematic analysis, revealing common themes and relationships between them across groups and implementations. The themes were categorised into three areas: (1) the societal functions of DIAL technologies, (2) the citizen types ("Subjects") shaped by DIAL, and (3) the societal tensions and contradictions arising around their use. Additionally, to explore the relationships between these themes we used network visualisation. This work contributes to the HCI field by providing the first study of its kind to explore the collective anticipations relate to futures of DIAL through participatory workshops. Furthermore, the emergent framework offers a broader contribution to HCI by providing a blueprint for portraying the implications of emerging technologies through collaborative speculation.
Mindtrek '25: Proceedings of the 28th International Academic Mindtrek